DAMAGE IDENTIFICATION SEGAH BRIDGE PIER DUE TO SHIP IMPACT - Aco Wahyudi Efendi (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2022)
Identification of damage or often referred to as on-site structural forensic testing, using visual observation methods and testing of existing materials using the Non Destructive Test method, in addition to check condition the geometry of the bridge after a ship hit. Conducted to determine the extent of damage to the Segah Bridge P2 pier after it was struck by a pontoon vessel carrying coal material across the Segah Bridge. To conduct this research, in addition to collecting data from the visual survey and some field testing, the results were analyzed using LISA FEA to determine the behaviors and stresses encountered during the incident. This investigation was conducted by collecting data from the on-site visual inspection followed by an inspection using the NDT tool to determine the material condition of the elements of the struck bridge, namely the P2 pierhead of the Segah Bridge. After collecting data, it proceeds by performing a microstructural analysis using the FEA software, namely LISA FEA V.8. From the results of the research and data processing, it can be seen that the damage behavior resulting from the numerical analysis using LISA FEA is very similar to the conditions in the field, which of course is obtained from very detailed and measurable parameters and data collection, so that the behavior corresponds to the actual state. Identifikasi kerusakan atau sering disebut dengan structural forensik testing, menggunakan metode observasi visual dan pengujian material yang ada menggunakan metode Non Destructive Test, selain untuk memeriksa geometri jembatan setelah ditabrak kapal. Dilakukan untuk mengetahui tingkat kerusakan dermaga P2 Jembatan Segah setelah ditabrak kapal ponton yang membawa material batubara melintasi Jembatan Segah. Untuk melakukan penelitian ini, selain mengumpulkan data dari survei visual dan beberapa pengujian lapangan, hasilnya dianalisis menggunakan LISA FEA untuk mengetahui perilaku dan tekanan yang dihadapi selama kejadian. Penyelidikan ini dilakukan dengan mengumpulkan data dari inspeksi visual di lapangan yang dilanjutkan dengan inspeksi menggunakan alat NDT untuk mengetahui kondisi material elemen jembatan yang tertimpa yaitu pierhead P2 Jembatan Segah. Setelah data terkumpul, dilanjutkan dengan melakukan analisis mikrostruktur menggunakan software FEA yaitu LISA FEA V.8. Dari hasil penelitian dan pengolahan data dapat diketahui bahwa perilaku kerusakan yang dihasilkan dari analisis numerik menggunakan LISA FEA sangat mirip dengan kondisi di lapangan, yang tentunya diperoleh dari parameter dan pendataan yang sangat detail dan terukur. , sehingga perilaku sesuai dengan keadaan sebenarnya.